Health-related quality of life and health state utility value in idiopathic pulmonary fibrosis: a systematic review and meta-analysis - Guixiang Zhao; Siyuan Lei; Ya Li; Zhenzhen Feng; Jiansheng Li (Health and Quality of Life Outcomes)
Abstract Background Idiopathic pulmonary fibrosis (IPF) is associated with high mortality, heavy economic burden, limited treatment options and poor prognosis, and seriously affects the health-related quality of life (HRQoL) and life expectancy of patients. This systematic review and meta-analysis of HRQoL and health state utility value (HSUV) in IPF patients and the instruments used in this assessment aimed to provide information sources and data support for the future research on IPF HRQoL and HSUV. Methods We searched the PubMed, EMBASE, Web of Science and Cochrane Library databases for studies reporting the HRQoL or HSUV of IPF patients, with the retrieval time from the establishment of each database to April 2024. After two researchers independently screened the literature, extracted the data, and evaluated the risk of bias in the included studies, pooled analysis was performed on the measurement tools adopted in more than two studies. Subgroup analysis was employed to explore the source of heterogeneity, and sensitivity analysis was used to assess the robustness of the results. Funnel-plot directed evaluation combined with Egger’s test quantitative evaluation was conducted to detect publication bias. Results Sixty-nine studies were ultimately included, covering eighteen measurement tools. The literature quality was generally excellent. The St. George’s Respiratory Questionnaire (SGRQ), EuroQoL Five Dimensions Questionnaire (EQ-5D), Short Form-36 (SF-36) and the King’s Brief Interstitial Lung Disease (KBILD) were the most common instruments, among which the EQ-5D included the HSUV and the visual analog scale (VAS). The results of the meta-analysis revealed that the pooled SGRQ total score was 45.28 (95% confidence interval [CI] 41.10-49.47), the mean EQ-5D utility score was 0.75 (95% CI: 0.72–0.79), the total EQ-5D VAS score was 66.88 (95% CI: 63.75–70.01), and the pooled SF-36 physical component summary (PCS) and mental component summary (MCS) score were 36.70 (95% CI: 32.98–40.41) and 48.99 (95% CI: 47.44–50.55), respectively. The total KBILD score was 58.31 (95% CI: 55.43–61.19), the IPF specific version of the SGRQ (SGRQ-I) was 40.38 (95% CI: 28.81–51.96) and the Leicester Cough Questionnaire (LCQ) score was 16.09 (95% CI: 15.45–16.74). The pooled result of the University of California San Diego Shortness of Breath Questionnaire (USCD-SOBQ) was 45.05 (95% CI: 41.56–48.55). The results of other instruments, such as the tool to assess quality of life in IPF (ATAQ-IPF), the World Health Organization Quality of Life assessment 100 (WHOQoL-100) and the 12-item short-form health survey (SF-12) were similar to those of the above measurement tools. Regretfully, subgroup analyses did not identify the source of heterogeneity, but sensitivity analyses demonstrated robustness of our results. Except for the SGRQ total, our results showed little possibility of publication bias. Conclusions HRQoL in IPF patients is generally poor, and all domains are severely affected. With the aggravation of disease, HRQoL and HSUV shows a relatively downward trend, and income level is also an important factor affecting HRQoL and HSUV. At present, the published studies on IPF HRQoL and HSUV have applied many measurement tools with high interstudy heterogeneity, and future research on the optimal disease measurement tools should be strengthened. Our study provides high-quality comprehensive evidence for IPF HRQoL and HSUV, which can be used to guide clinical and economic evaluation in the future.